Hypoxia-inducible factor 1 alpha expression is an indicator of invasiveness in uterine cervical tumors - Ayaz, Duygu; Diniz, Gülden; Kahraman, Dudu Solakoğlu; Sayhan, Sevil; Kahraman, Duygu; Karadeniz, Tuğba (International Journal of Research in Medical Sciences, 2019)
Background: Hypoxia is a common feature of cancers. Hypoxia-inducible factor 1A (HIF1A) is a causative agent that changes the transcriptional response of tumors under hypoxia. Some alterations lead to an increase in HIF1A activity and this supports other critical pathways leading to angiogenesis, metabolic adaptation and tumor progression. This retrospective study was designed to evaluate the differences of tissue expressions of HIF1A in a spectrum of cervical neoplasms. Methods: Tissue expression of HIF1A was studied in a total of 107 formalin-fixed, paraffin-embedded uterine cervical tumors specimens and its association with different clinicopathologic parameters was evaluated. Results: In this series, there were 30 low and 29 high grade cervical intraepithelial neoplasms (CINs), 27 squamous cell carcinomas, 15 adenosquamous carcinomas and 6 adenocarcinomas. Strong and diffuse nuclear staining was evaluated as positive HIF1A expression. Positive HIF-1 alpha expression was detected in 7 (25.9%) of squamous cell carcinomas, 1 of adenocarcinomas (16.7%) and only 1 of HGSILs (3.4%). Statistically it was determined that the positivity rate of strong nuclear HIF1A expression was significantly higher in invasive carcinomas when compared with in non-invasive squamous cell carcinomas (p=0.07). Contrary, there was no statistically significant difference according to the subtypes of carcinomas due to scarce number of cases with adenocarcinoma (p=0.188). Conclusions: Our findings were demonstrated to link of nuclear HIF1A expression and the invasive characters of uterine neoplasms. As a result, HIF-1 alpha expression may be important in foreseeing of the invasion and tumor progression.